A 7-nm-Based 5R4W High-Timing Reliability Regfile Circuit - Wanlong Zhao; Yuejun Zhang; Liang Wen; Pengjun Wang (IET Circuits, Devices and Systems)
Register file (Regfile), as the bottleneck circuit for processor data interaction, directly determines the computing performance of the system. To address the read/write conflict and timing error problems of register heap, this paper proposes a 5R4W high-timing reliability Regfile circuit design scheme. First, the scheme analyzed the principles of timing errors such as read/write conflicts, write errors, and read errors in the Regfile circuit; then adopted the timing separation method of independent control of the read/write process by clock double edges to solve multiport read/write conflicts, designed a mirror memory check circuit to avoid write errors caused by the word line delays, and used a phase-locked clock feedback structure to eliminate read errors caused by the data timing fluctuations; in the TSMC 7 nm FinFET process, a 64 × 74-bit 5R4W Regfile circuit was implemented using a fully customized layout. Experimental results show that the Regfile circuit has an area of 0.13 mm2 and consumes 5.541 mW. The circuit operates at a maximum frequency of 3.8 GHz at −40 to −125°C and 0.75 V, and is capable of detecting write errors caused by a clock jitter exceeding 30 ps or a frequency above 5 GHz.